55.2k views
5 votes
Rewrite the equation by completing the square. X2−2x+1=0x^{2}-2x+1 = 0x2−2x+1=0x, squared, minus, 2, x, plus, 1, equals, 0 (x+(x + {}(x+left parenthesis, x, plus )2=)^2 = {})2=right parenthesis, squared, equals

1 Answer

3 votes

Rewriting
2x^2-2x+1=0 equation we get
(x-1) ^2=0.

Given the quadratic equation


2x^2-2x+1=0

the process of completing the square involves manipulating the equation to a form that expresses a perfect square trinomial.

First, move the constant term to the right-hand side, resulting in


x^2 −2x−1=0.

Next, halve the coefficient of x, yielding

−2/2=−1

Squaring this result
(-1)^2 gives 1.

Add this value to both sides of the equation:

=
x^2 −2x +
(-1) ^2

= −1 +
(-1) ^2

leading to


(x-1) ^2=0

Upon simplification,

x−1 squared equals zero.

Therefore, the equation rewritten by completing the square is


(x-1) ^2=0, indicating that the solution involves a perfect square binomial with a value of zero.

User Oded Harth
by
4.4k points